Effects of limited introgressions from Triticum timopheevii Tausch. into the genome of bread wheat (Triticum aestivum L.) on physiological and biochemical traits under normal watering and drought - T. A. Pshenichnikova; A. V. Permyakov; S. V. Osipova; M. D. Permyakova; E. G. Rudikovskaya; V. V. Verchoturov (Вавиловский журнал генетики и селекции)
Alien hybridization in cereals is used for comparative investigations of genome structure and evolution as well as for extracting useful genes from the wild gene pool. The tetraploid species Triticum timopheevii has long been used as a source of genes for resistance to fungal diseases. Line 821 was developed on the genetic background of cultivar Saratovskaya 29 (S29), which is drought-resistant but is very susceptible to diseases and carries big introgressions in 2A and 2B chromosomes and a small introgression in the subtelomeric region of 5A chromosome. The two genotypes were compared for the parameters associated with direct and indirect reaction of the photosynthetic apparatus to water stress. In flag leaves of 821 line, an increased transpiration rate and stomatal conductance (1.6 times the value in optimal watering and 1.2 times the value under water deficit) and, correspondingly, reduced water use efficiency were found compared to the initial cultivar. Additionally, the actual effectiveness and electron transport rate of photosystem II and chlorophyll and carotenoid content were reduced as well as the total antioxidant capacity (approximately three-fold) under water stress. Under the same conditions, lipoxygenase activity was increased two-fold. On the whole, water deficit tolerance was decreased in the line in comparison with the parental cultivar and was accompanied by leaf senescence. Thus, it may be supposed that 2A, 2B and 5A chromosomes of the drought-tolerant cultivar S29 carry important genetic factors responsible for reaction to water stress in wheat plants.